Carbon Dioxide Decomposition by a Parallel-Plate Plasma Reactor: Experiments and 2-D Modelling - Ali Barkhordari (MDPI AG, 2021)
The applicability of high voltage electrical discharges for the decomposition of CO2 has been extensively demonstrated. In this study, a new AC parallel-plate plasma reactor is presented which was designed for this purpose. Detailed experimental characterization and simulation of this reactor were performed. Gas chromatography of the exhaust gases enabled calculation of the CO2 conversion and energy efficiency. A conversion factor approximating 25% was obtained which is higher in comparison to existing plasma sources. Optical emission spectroscopy enabled the determination of the emission intensities of atoms and molecules inside the plasma and characterization of the discharge. The Stark broadening of the Balmer hydrogen line Hβ was used for the estimation of the electron density. The obtained densities were of the order of 5 × 1014 cm−3 which indicates that the electron kinetic energy dominated the discharge. The rotational, vibrational, and excitation temperatures were determined from the vibro-rotational band of the OH radical. A 2-temperature plasma was found where the estimated electron temperatures (~18,000 K) were higher than the gas temperatures (~2000 K). Finally, a 2-D model using the fluid equations was developed for determining the main processes in the CO2 splitting. The solution to this model, using the finite element method, gave the temporal and spatial behaviors of the formed species densities, the electric potential, and the temperatures of electrons.